Elaboration and Biocompatibility of an Eggshell-Derived Hydroxyapatite Material Modified with Si/PLGA for Bone Regeneration in Dentistry - Sandra Janeth Gutiérrez-Prieto; Luis F. Fonseca; Luis Gonzalo Sequeda-Castañeda; Kelly J. Díaz; Linet Y. Castañeda; José A. Leyva-Rojas; Juan Carlos Salcedo-Reyes; Adriana P. Acosta (Hindawi Limited, 2019)
Hydroxyapatite (HAp) is the most commonly used biomaterial in modern bone regeneration studies because of its chemical similarity to bone, biocompatibility with different polymers, osteoconductivity, low cost, and lack of immune response. However, to overcome the disadvantages of HAp, which include fragility and low mechanical strength, current studies typically focus on property modification through the addition of other materials. Objective. To develop and evaluate the biocompatibility of a HAp material extracted from eggshells and modified with silicon (Si) and poly(lactic-co-glycolic) acid (PLGA). Materials and Methods. An in vitro experimental study in which a HAp material prepared from eggshells was synthesized by wet chemical and conventional chemical precipitation. Subsequently, this material was reinforced with Si/PLGA using the freezing/lyophilization method, and then osteoblast cells were seeded on the experimental material (HAp/Si/PLGA). To analyse the biocompatibility of this composite material, scanning electron microscopy (SEM) and fluorescence confocal microscopy (FCM) techniques were used. PLGA, bovine bone/PLGA (BB/PLGA), and HAp/PLGA were used as controls. Results. A cellular viability of 96% was observed for the experimental HAp/Si/PLGA material as well as for the PLGA. The viability for the BB/PLGA material was 90%, and the viability for the HAp/PLGA was 86%. Cell adhesion was observed on the exterior surface of all materials. However, a continuous monolayer and the presence of filopodia were observed over both external and internal surface of the experimental materials. Conclusions. The HAp/Si/PLGA material is highly biocompatible with osteoblastic cells and can be considered promising for the construction of three-dimensional scaffolds for bone regeneration in dentistry.